The Pu.1 target gene Zbtb11 regulates neutrophil development through its integrase-like HHCC zinc finger - Maria-Cristina Keightley (Nature Portfolio, 2017)
Neutrophils are increased in response to injury and infection but how they form from a common granulocyte-macrophage progenitor is unclear. Here, the authors identify a role for the transcriptional repressor ZBTB11 in zebrafish, which is regulated by master myeloid regulators and repressesTP53.